HYBRID TEACHER TRAINING: THE CONSTRUCTION OF PEDAGOGICAL PRACTICE AS ARTICULATOR AXIS FOR THE USE OF TECHNOLOGIES IN AN INCLUSIVE SCHOOL - Danielle Aparecida do Nascimento dos Santos; Elisa Tomoe Moriya Schlünzen; Renata Portela Rinaldi (Revista Gestão & Saúde, 2013)
This paper aims to present data related to the preparation, implementation, monitoring, development and evaluation of Articulator Axis: Inclusion and Special Education of hybrid Pedagogy UNIVESP/UNESP course. It is explained the theoretical, methodological and practical contributions that supported the organization of the discipline, designed with the premise to train teachers in order to provide analysis tools on the policies and practices of school inclusion of students of Special Education. As well as offering elements to teachers who attend the course for an analysis of practices and resources that can be used in the context of an inclusive school, through the promotion of school activities that develop the skills of all. The discipline was developed in five (5) blocks of 24 (twenty four) hours per week, which were proposed activities and studies on the activities related to elementary and high school, aggregated to Specialized Educational Service and the use of Digital Information and Communication Technologies, according to the specific educational needs of students of Special Education and considering its importance within the policies of inclusion and its application in school contexts linked to the disciplines of didactic contents of the course.